2021
DOI: 10.1159/000517415
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Literature on Cerebral Bypass Surgery: A Systematic Review

Abstract: <b><i>Introduction:</i></b> Ever since the beginning of cerebral bypass surgery, the role of the bypass has been debated and indications have changed over the last 5 decades. This systematic literature research analysed all clinical studies on cerebral bypass that have been published from January 1959 to January 2020 for their year of publication, country of origin, citation index, role of and indication for bypass, bypass technique, revascularized territory, flow capacity, and title (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Bypass surgery is effective for the treatment of chronic steno‐occlusive vasculopathy (CSOV) by reducing the risk of future stroke, reducing frequency of transient ischemic attacks, and improving long‐term cognitive function and activities of daily living. 1 , 2 , 3 The surgery is recommended to be performed as soon as it can be reasonably scheduled after the acute phase. 4 , 5 Nevertheless, not all patients benefit from this gold‐standard surgery due to postoperative ischemia, hyperperfusion syndrome (HPS) and other unknown reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Bypass surgery is effective for the treatment of chronic steno‐occlusive vasculopathy (CSOV) by reducing the risk of future stroke, reducing frequency of transient ischemic attacks, and improving long‐term cognitive function and activities of daily living. 1 , 2 , 3 The surgery is recommended to be performed as soon as it can be reasonably scheduled after the acute phase. 4 , 5 Nevertheless, not all patients benefit from this gold‐standard surgery due to postoperative ischemia, hyperperfusion syndrome (HPS) and other unknown reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Extracranial to intracranial bypass surgery for flow augmentation in MMD has been performed mostly in Asian countries due to its pathological entity, and research is increasing every year. 7 To our knowledge, only one Japanese trial has revealed that bypass surgery in adult patients with hemorrhagic moyamoya reduces recurrent bleeding or related death or severe disability with marginal significance. 8 Regarding patients with ischemic or asymptomatic MMD, there have been no randomized trials.…”
mentioning
confidence: 99%